The seroperevalence of bovine brucellosis in two locations in Colombia’s Caribbean region (Orinoquia, 2015)
The prevalence of bovine brucellosis varies considerably from country to country; the rates recorded in Latin-America range from 0.5 to 10%. The current seroprevalence rate for brucellosis in cattle in Colombia is estimated as being between 2.4% and 5%. A descriptive epidemiological cross-sectional study was carried out in rural areas near the towns of Pijiño del Carmen (Magdalena department) and María la Baja (Bolívar department) for estimating bovine brucellosis seroprevalence in two locations in Colombia’s Caribbean region. This involved collecting 246 samples of bovine sera for diagnosing brucellosis by the Rose Bengal test (RBT), positive sera being confirmed by C-ELISA test. The RBT gave 11% seroprevalence in Pijiño del Carmen and C-Elisa 6% whilst RBT gave 1.36% and C-Elisa 0.68% in María la Baja. Seroprevalence studies in regions where the susceptible animals’ population density is high should provide an insight into the pertinent epidemiology and lead to prevention and control measures being brought into force.Key words: Antibody; cattle; Brucella abortus; diagnosis;  serology
Keywords: Antibody; cattle; Brucella abortus; diagnosis; serology